Institutional Vulnerability, Breakdown of Trust: A Model of Social Unrest in Chile - Velasco, Andrés; Funk, Robert (Estudios de Economía, 2025)
This paper revisits the standard explanations of the violent Chilean protests of late 2019, and in particular their exclusive focus on the role of inequality, which in fact had been falling prior to the emergence of unrest. Instead, we suggest that blame may lie in a crisis of trust in institutions, political and otherwise. We employ a formal model of how trust in government institutions can arise —and also disappear— overnight. In that model, the level of trust is tied (but not uniquely tied) to the level of civic capital in a society. If civic capital is above a certain threshold, then trust can only be high and increasing, but if civic capital is below that threshold, then the outcome is indeterminate, meaning the level of trust is vulnerable to self-fulfilling bouts of optimism or pessimism. The threshold for civic capital can be shifted by exogenous shocks to parameter values, including the quality of institutions, with the consequence that small shocks can have small and lasting effects if they take the system from one region to another. We document how these dynamics resemble the facts from Chile, where a small drop in reported institutional quality was associated with a large drop in measured trust around the time of the protests. In turn, the protests involved patterns of behavior (like the destruction of urban infrastructure, the evasion of user fees in buses and trains, and the non-repayment of student loans) which further deteriorated the capacity of the state to provide certain quality public services, and aggravated the decline in institutional trust.